(untitled) (Bulletin of criminological association of Ukraine, 2024)
It was found that the subjects of preventive activity are a set of state authorities and their officials, as well as structural subdivisions of the police, which are endowed with the necessary competence and powers to implement special measures and perform a special type of actions aimed at prevention, defined by the norms of current legislation , preventing and preventing violations of the rule of law in the state, as well as the rights, freedoms and interests of a person and a citizen. It is argued that the subject structure of preventive activity includes three groups: 1) the Verkhovna Rada of Ukraine, the Cabinet of Ministers of Ukraine, the Ministry of Internal Affairs of Ukraine - subjects of ensuring and creating conditions for the implementation of preventive activities of the National Police; 2) local state administrations and local self-government bodies – subjects of support and assistance in the implementation of preventive activities by the National Police of Ukraine; 3) specially authorized bodies and units of the National Police of Ukraine are the key actors of prevention, which are responsible for the actual implementation of special measures, means, operations and actions aimed at the prevention, prevention and prevention of violations of the rule of law, human and citizen rights and freedoms. It is emphasized that the peculiarity of each subject of all three groups is that they have the opportunity to enter into administrative and legal relations on issues of provision, organization and implementation of preventive activities, they have the opportunity exclusively in accordance with their competence and powers, which are of a heterogeneous nature and are strictly regulated by legislation of Ukraine.